Global, regional, and national prevalence and determinants of volunteer work: a meta-analysis study using survey data - Samuel Manda; Nada Abdelatif; Dineo Seabe; Sollie Millard; Tapiwa Kamuruko (Frontiers in Sociology)
IntroductionWhile there is an increasing recognition of the role of volunteer work in promoting global development, the factors influencing volunteering at both global and regional levels remain poorly understood. This study employed a random-effects meta-analysis to estimate the prevalence of volunteering and to investigate variations in volunteer rates by gender, educational level, and age, both globally and at regional and country levels.MethodsWe analyzed data from 49,458 volunteers aged 15 and older across 37 World Values Surveys (WVS) conducted between 2000 and 2018 in 31 countries. Random-effects meta-analysis was employed to calculate the overall prevalence of volunteering and to compare volunteer rates among different demographic groups: females vs. males, individuals with at least a secondary education vs. those with primary education or less, and individuals aged 35 years or older versus those under 35 years.ResultsThe overall pooled prevalence of volunteering was found to be 39.93% (95% CI: 33.25–46.62). Significant disparities in volunteering rates were observed across regions and countries, with the highest rates recorded in Africa (61.15%, CI: 50.54–77.77) and the lowest in Europe (28.97%, CI: 19.43–38.51). Rates varied considerably, from a low of 19.16% in Russia (CI: 19.16%–22.76%) to a high of 80.27% in Tanzania (CI: 77.99–82.55%) and 72.00% in Uganda (CI: 69.18–76.22%). Volunteering in religious organizations was the most common type, accounting for 16.77% (CI: 13.76–19.78), followed by community and health organizations at 14.62% (CI: 11.74–17.50). Regional differences were notable, with the highest rates of religious volunteering in Africa at 41.09% (CI: 20.17–62.02) and the lowest in Europe at 8.10% (CI: 5.25–10.95). The pooled relative risks for gender, educational, and age differentials were (RR = 0.91, 95% CI: 0.86–0.97); (1.20, CI: 1.18–1.36); and (1.00, CI: 0.95–1.05), respectively, indicating that only educational differentials significantly affected volunteering rates. The impact of education on volunteering was more pronounced in Europe (1.54, CI: 1.21–1.97) compared to Africa (1.17, CI: 1.03–1.33).ConclusionsVolunteering rates vary significantly by region and country, often correlating with individuals' educational levels. These findings are essential for policymakers aiming to enhance volunteer initiatives. By understanding the regional contexts and factors, such as the influence of education level on volunteering, policymakers can develop tailored programs that attract new volunteers and promote retention, ultimately fostering greater community engagement and social cohesion.